Access to thiazoline and spiro[indoline-3, 3′-thiophene] scaffolds via a formal [3 + 2] annulation reaction of crotonate-derived sulfur ylides and β-ketothioamides. Issue 10 (20th February 2023) - Zheng, Jing; Gu, Hong; Chen, Qinfang; Yang, Weiran
Abstract : A formal [3 + 2] annulation reaction of crotonate-derived sulfur ylides and β-ketothioamides (KTAs) was successfully developed to produce good-to-excellent yields of thiazoline and spiro[indoline-3, 3′-thiophene] scaffolds. Abstract : A formal [3 + 2] annulation reaction of crotonate-derived sulfur ylides and β-ketothioamides (KTAs) was successfully developed to produce good-to-excellent yields of thiazoline and spiro[indoline-3, 3′-thiophene] scaffolds. This transformation is a powerful tool for the synthesis of thiazoline and spiro[indoline-3, 3′-thiophene] scaffolds due to its mild reaction conditions, easily accessible starting materials, and broad substrate scope. A large-scale reaction was carried out to ensure the practical applicability of this methodology. Finally, the plausible mechanistic pathway of the developed methodology was investigated.